Rational Choices of Labor Workers in Increasing Family Income in Indonesia Forest Fringe Communities - Tamrin Bangsu; Yunilisiah Yunilisiah; Yuli Hartanto (Universitas Pendidikan Ganesha, 2023)
This study aims to describe the Rational Choices of Labor Workers in increasing family income in forest fringe communities. The method used is qualitative descriptive with an ethnographic approach; informants consist of laborers and landowners. Data collection techniques are carried out by participant observation, interviews, and documentation; data analysis is carried out by Interactive analysis, namely with three flow processes: data reduction, data presentation, and data verification. The study results show that labor is the main job for people who do not have land; the selection of work as a laborer is motivated by economic factors, and they do not have land to cultivate themselves. The income obtained by workers is only enough for daily food, so this work greatly supports the survival of people who work as laborers to meet their daily needs, only relying on daily work with wages of Rp.50,000 to Rp.80,000. Women have a dual role in helping the family economy. Women work as laborers to help meet the daily needs of the family. Labor efforts increase income by working in two places, thus increasing family income.